2018
DOI: 10.1128/iai.00111-18
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HMGB1 Neutralizing Antibody Attenuates Periodontal Inflammation and Bone Resorption in a Murine Periodontitis Model

Abstract: High mobility group box 1 (HMGB1) is a non-histone DNA-binding protein that is secreted into the extracellular milieu in response to inflammatory stimuli. The secreted HMGB1 mediates various inflammatory diseases, including periodontitis; however, the underlying mechanisms of HMGB1-induced periodontal inflammation are not completely understood. Here, we examined whether anti-HMGB1 neutralizing antibody inhibits periodontal progression and investigated the molecular pathology of HMGB1 and analysis indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…According to Wolf et al's research, HMGB1 shows a RANKL-related activity in regulating periodontal remodeling during orthodontic tooth movement in rats [42]. Yoshihara-Hirata et al found that HMGB1 was involved in the development of periodontitis and anti-HMGB1 antibody treatment attenuated alveolar bone absorption and the progression of periodontitis [43]. These results provide strong support for this study.…”
supporting
confidence: 78%
“…According to Wolf et al's research, HMGB1 shows a RANKL-related activity in regulating periodontal remodeling during orthodontic tooth movement in rats [42]. Yoshihara-Hirata et al found that HMGB1 was involved in the development of periodontitis and anti-HMGB1 antibody treatment attenuated alveolar bone absorption and the progression of periodontitis [43]. These results provide strong support for this study.…”
supporting
confidence: 78%
“…Interestingly, several functional aspects of HMGB1 might be relevant to the periodontal and scarring phenotypes observed in pEDS patients. For example, several studies in rodents and humans suggest a significant role of HMGB1 in periodontal inflammatory infiltration and alveolar bone destruction or resorption (23,24). Normal human oral mucosa is continuously prone to micro-tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is secreted in response to inflammatory stimuli caused by periodontal infection, which is crucial for the initiation of periodontitis. The anti‐HMGB1 antibody reduces the secretion of a series of inflammatory cytokines, consequently suppressing the progression of periodontitis (Yoshihara‐Hirata et al., ). Overall, these data are consistent with the beneficial effects of biological agents on the periodontal parameters as observed with humanized anti‐TNFα monoclonal antibody, adalimumab (Kobayashi et al., ) and infliximab (Mayer, Balbir‐Gurman, & Machtei, ) on the periodontal condition of patients with rheumatoid arthritis.…”
Section: Preamblementioning
confidence: 99%